2020
DOI: 10.1038/s41419-020-02986-w
|View full text |Cite
|
Sign up to set email alerts
|

The antitumour drug ABTL0812 impairs neuroblastoma growth through endoplasmic reticulum stress-mediated autophagy and apoptosis

Abstract: Neuroblastoma is the leading cause of cancer death in children aged 1 to 4 years. Particularly, five-year overall survival for high-risk neuroblastoma is below 50% with no curative options when refractory or relapsed. Most of current therapies target cell division and proliferation, thereby inducing DNA damage and programmed cell death. However, aggressive tumours often present alterations of these processes and are resistant to therapy. Therefore, exploring alternative pathways to induce tumour cell death wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Therefore, the aggressiveness and poor prognosis of TNBC call for new and more effective therapies.ABTL0812 is a novel first-in-class anticancer agent. It was initially selected for preclinical development based on its anti-proliferative effect on different human cancer cell lines and its safety profile in animal models as both single therapy and in combination with chemotherapy [4][5][6][7][8]. A first-in-human phase I clinical trial with ABTL0812 was successfully completed, showing a high safety profile and signs of efficacy in patients with advanced solid tumors who had received ABTL0812 orally after several chemotherapy lines (NCT02201823).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aggressiveness and poor prognosis of TNBC call for new and more effective therapies.ABTL0812 is a novel first-in-class anticancer agent. It was initially selected for preclinical development based on its anti-proliferative effect on different human cancer cell lines and its safety profile in animal models as both single therapy and in combination with chemotherapy [4][5][6][7][8]. A first-in-human phase I clinical trial with ABTL0812 was successfully completed, showing a high safety profile and signs of efficacy in patients with advanced solid tumors who had received ABTL0812 orally after several chemotherapy lines (NCT02201823).…”
mentioning
confidence: 99%
“…It can induce endoplasmic reticular (ER) stress and inhibit the protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) axis via the overexpression of tribbles homolog 3 (TRIB3). These two actions converge to strongly induce cytotoxic autophagy that can cause cancer cell death, while non‐tumor cells are spared [ 4 , 5 , 6 , 7 , 8 ]. Deregulation of the phosphoinositide 3‐kinase (PI3K)/Akt/mTOR (PAM) signaling pathway is a common oncogenic aberration observed in TNBC that frequently leads to chemoresistance [ 1 ].…”
mentioning
confidence: 99%
“…We further confirmed that the autophagy inhibitors 3-MA and CQ moderately reversed the inhibitory effect of the combination of sorafenib and TMZ on the cell apoptosis rate ( Figure 6D ), indicating that the combined therapy induces cell apoptosis through the induction of autophagy. Autophagy and apoptosis can trigger cell death through synergistic action and complementary cooperation ( París-Coderch et al, 2020 ). The proapoptotic effect of autophagy caused by the combined therapy also indicated that autophagy and apoptosis caused by combined therapy had synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Following the rational drug design, C2-hydroxylated fatty acids have been developed to treat several conditions. Examples of advanced clinical development in this regard are 2-hydroxyoleic acid (LAM561), which has shown safety and promising therapeutic activity against glioma and other types of tumor in humans [50,113], and 2-hydroxylinoleic acid (ABTL0812), which has demonstrated safety and efficacy against endometrial and lung cancers [143,144] (reviewed below). On the other hand, another DHA hydroxylated analog with therapeutic properties is 2-hydroxydocosahexaenoic acid (DHA-H), which has been demonstrated to have neuroprotective and neuroregenerative activity, and to be safe and efficacious in mouse models of AD and Parkinson's disease (PD) in preclinical studies (PCS) [114,145] (reviewed below).…”
Section: Natural Bioactive Lipids and Rational Design Of Lipid Bilayer-targeted Therapiesmentioning
confidence: 99%
“…Similarly, 2-hydroxylinoleic acid (ABTL0812) has been demonstrated to be safe and efficacious against endometrial and lung cancers, both in model systems and in clinical trials (NCT02201823, NCT03366480, NCT03417921, NCT04431258), producing specific cancer cell death. Thus, ABTL0812 binding to the membrane inhibits Akt/mTORC1, enhances sphingolipid dihydroceramide activity, provoking ER stress and autophagic cell death without inducing undesired side effects [143,144].…”
Section: Lipid Therapies In Cancermentioning
confidence: 99%